Effectiveness of Chinese Ketepeng Infusion on Streptozotocin-Induced Mice - Watuguly, Theopilus Wilhelmus; Pattiasina, Eifan Boyke (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Blood sugar is a metabolic disorder disease that occurs due to insufficiency of insulin hormone production or due to insulin insensitivity resulting in typical clinical manifestations in the form of increased glucose levels in the blood (hyperglycemia). This study aims to determine the effect of Chinese ketepeng leaf decoction on blood glucose levels in hyperglycemic mice. This research was carried out in the Zoology laboratory, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon. This research is an experimental laboratory with a pre and post-test research design with a control group design. This study wanted to prove whether there was an effect of giving Chinese ketepeng leaf decoction to decreasing blood sugar levels in male Balb/C mice using Chinese ketepeng leaf decoction at a dose of 3.64 mg/kg, 7.28 mg/kg, 10.92 mg/kg. The results showed that the usage of Chinese ketepeng leaves (Cassia alata L) can reduce blood sugar levels in mice (Mus musculus). The most effective dose to lower blood sugar levels is a dose of 10.92 mg/kg BW.